Financial Inclusion and Electronic Defense in Iraq: Challenges and Opportunities Intervention Title: A Quantitative Model of the Effect of Financial Inclusion on the Unemployment Rate in Algeria Using the ARDL Model During Eid 2004–2 - Obaid, Asst.Prof.Dr.Muhannad Khalifa Obaid; Laila, Dr.Awlad Ibrahim Laila; Khadija, T. Karami Khadija; Jamal, Dr. Daqish Jamal (Sulaimani Journal for Humanities, 2026)
This study aims to analyze the impact of financial inclusion on the unemployment rate (social dimension) in Algeria during the period 2004–2022, using the Autoregressive Distributed Lag (ARDL) model to measure the relationship in both the short and long run. The study employed two methodologies: a descriptive approach, reviewing theoretical literature on financial inclusion and social development, and an applied quantitative approach using data from the Bank of Algeria and the World Bank. Statistical tools such as the stability test, the bounds test for cointegration, the long-run model, and the ECM (Error Correction Coefficient) were utilized. The results showed that the relationship between financial inclusion and the unemployment rate (social dimension) is not uniform. Credit extended to the private sector was the most significant variable in improving the social indicator (unemployment rate) in the long run, while the impact of bank branches and ATMs was limited and insignificant, with short-term negative repercussions from sudden changes in credit. The ECM also confirmed a long-run equilibrium relationship between the variables and a rapid return to equilibrium after imbalances. Based on these results, the study recommended the need to redirect financial policies to serve social inclusion, through the digitization of financial services and their expansion towards remote areas, encouraging electronic payment and financial innovation, reducing the costs of banking transactions for low-income groups, in addition to promoting financial literacy and partnership between the banking sector and social institutions to finance small and medium-sized enterprises aimed at reducing unemployment and improving basic services.
Keywords: Financial inclusion; social development; financial integration; Algeria